Economic Analysis of Law Pada Perubahan Kebijakan Kontrak Karya Menjadi Ijin Usaha Pertambangan Khusus (IUPK): Studi Kasus Pt. Freeport Indonesia - Isti Sulistyorini; Siti Zulaekhah (Pena Justisia: Media Komunikasi dan Kajian Hukum, 2017)
Freeport Indonesia is the first Indonesian PMA company in the field of mineral mining which has been operating its business activities since 1968, at the time of enactment of Law no. 1 Year 1967 about PMA. Political turmoil and economic instability, low exchange rate and social conflicts are a burden to the government and demand a swift step to overcome them. As a potential economic sector deemed capable of sustaining state revenues to be distributed to the public and ultimately improving the welfare of the people, the mining sector receives serious attention. Based on author literature search, PT. Freeport Indonesia is the first Indonesian PMA company in the field of mineral mining which has been operating its business activities since 1968, at the time of enactment of Law no. 1 Year 1967 about PMA. Based on the economic analysis of law according to Richard A. Postner, the change of the mining concession policy from contract-based in the form of Contract of Work (KK) to license-based through a Special Mining Business License (IUPK) is in accordance with the economic approach to the law. Government of Indonesia gradually over its attitude that the renewal of mining concession mechanism that is more oriented to the greatest prosperity of the people.Keywords: Economic Analysis Of Law, Contract of Work, Freeport